Children Australia–A 40 Year Retrospective of Australian Out-of-Home Care: Reflections of the Past and Future Directions. (20th October 2015) - Vicary, Dave
Abstract : For 40 years, Children Australia (and previous incarnations) has provided an enormously valuable space for research, practice and policy to delineate challenges, successes and innovation on issues pertaining to the wellbeing and welfare of children and their families. Articles published in the Journal during this period have been incredibly influential and have added to our collective knowledge of children, young people and their families. Nowhere has this been more evident than the area of out-of-home care (OOHC). This paper will explore and reflect on some of the issues that have been articulated in papers published in the journal over the last 40 years – with a specific focus on Australian Kinship, Foster, Residential and Therapeutic Residential Care. Past issues that are still presenting current challenges will be described and opportunities for change and future improvement identified.